Pola Pengelolaan Kekayaan Nagari Dan Pemberdayaan Masyarakat Dalam Peningkatan Kesejahteraan - Lerri Pattra (Nagari Law Review, 2021)
One of the objectives of a state is stated in the fourth paragraph of the preamble to the 1945 Constitution, namely for the welfare of the community. After the enactment of the Regional Government Law, regional governments were given the authority to regulate and manage their own regional government affairs. The existence of nagari as a legal community unit in the Unitary State of the Republic of Indonesia has a constitutional basis in Article 18 B paragraph (2) of the 1945 Constitution, the article states "The state recognizes and respects the unity of customary law communities and their traditional rights ...". Before the amendment of the 1945 Constitution, Nagari was recognized as an area with original and special rights. Nagari as the lowest government unit that directly deals with the people in West Sumatra, in its development, is required to be able to empower and provide increased welfare for its people. An important aspect of Nagari autonomy is the authority to regulate (regularend) the household in the form of a legal product known as Nagari Regulation. With the existence of rules, the second aspect of autonomy will be implemented, namely the aspect of managing (besturen). Aspects of regulating according to the authority of the Nagari stipulated in the Nagari Government Law (a) authority based on rights of origin, (b) Village-scale local authority; (c) authority assigned by the Government, Provincial Government, or Regency / Regional Government City; and other authorities assigned by the Government, Provincial Government, or Regency / City Regional Government in accordance with the provisions of statutory regulations. Good management of village wealth and community empowerment will be able to improve community welfare, according to the aspirations of the Indonesian nation